Treatment of Concurrent Thrombotic Thrombocytopenic Purpura and Graves' Disease: A Report on Two Cases. (9th August 2018) - Lhotta, Karl; Zitt, Emanuel; Sprenger-Mähr, Hannelore; Loacker, Lorin; Becherer, Alexander
Abstract : Graves' disease (GD) and thrombotic thrombocytopenic purpura (TTP) are autoimmune diseases caused by autoantibodies against the TSH receptor (TRAb) and the enzyme ADAMTS13. We here report on two patients with concurrent GD and TTP, who achieved sustained remission of both conditions with the TTP treatment regimen and thiamazole. Both patients suffered from relapsing TTP and were diagnosed with GD concomitantly at the time of relapse. They were treated with steroids, plasma exchange, rituximab, and thiamazole. This therapy induced complete remission of TTP. TRAb levels also decreased rapidly and both patients developed subclinical hypothyroidism three and five weeks later. Our observations suggest that TTP and GD may be concomitant and that GD possibly triggers a relapse of TTP. The combination of thyrostatic treatment and immunosuppression with PE, rituximab, and steroids is able to induce rapid and prolonged remission of GD.